Aboriginal Knowledges in Specialized Courts: Emerging Practices in Gladue Courts. Issue 3 (20th December 2016) - Maurutto, Paula; Hannah-Moffat, Kelly
Abstract: Reforms to Canadian sentencing law in 1996 and the Supreme Court of Canada decision R. v. Gladue [1999] opened the door to a new normative set of legal practices that endeavour to integrate racial knowledge about offenders' collective and individual experiences of race relations and oppression into traditional legal criminal practices. One outcome of the reforms and court cases was the formation of dedicated Gladue courts for Aboriginal peoples. This paper explores the formation of Gladue courts, the legal techniques used to produce contextualized racial knowledges, how this information is admitted as evidence before the court, and how this knowledge is used to reframe legal subjects and the risk they pose. Résumé: Des réformes apportées en 1996 aux lois concernant la détermination de la peine, ainsi que la décision R. c. Gladue de 1999 de la Cour suprême du Canada, ont ouvert la voie à un nouvel ensemble de pratiques normatives visant à intégrer aux pratiques pénales traditionnelles les connaissances sur les expériences collectives et individuelles du contrevenant en matière de relations et d'oppression raciales. L'un des résultats de ces réformes et affaires a été la création de tribunaux Gladue spéciaux pour les personnes autochtones. Cet article examine la création des tribunaux Gladue, les techniques juridiques employées pour obtenir des connaissances raciales contextualisées, la façon par laquelle cette information est prise en compte par la Cour, et la façon par laquelle ces connaissances sont appliquées pour resituer les sujets juridiques et les risques qu'ils posent.